VARIATION AMONG ISOLATES OF F.SP. FUSARIUM OXYSPORUM CICERI CAUSING CHICKPEA WILT (Journal of Plant Disease Sciences, 2017)
Chickpea ( L.) one of Cicer arietinum  the most important pulse crops grown in Asian  subcontinent, third most important food  legume of the world. Maharashtra contributes  about 10 per cent share in total production of  country. One of the major production  constraints in chickpea is wilt Fusarium caused by f.sp Fusarium oxysporum . ciceri (Jalali and Chand, 1992). The disease is wide  spread in chickpea growing areas of the world  and is reported from 33 countries The  pathogen penetrates the roots and provokes  either root rots or tracheomycosis when they  invade the vascular system, causing wilt  disease. The disease can be observed in  susceptible cultivar within 25 days after  sowing in infected soil and this known as  'early wilt' (Haware 1980). Wilting may et al., also occur during reproductive growth and is  known as 'late wilt'. Fusarium oxysporum f.sp. is highly variable pathogen. ciceri The  present study was conducted to understand  the cultural and morphological variability  among isolates of f.sp. Fusarium oxysporum ciceri, collected from different locations of  Maharashtra.
Keywords: Fusarium oxysporum . ciceri, Chickpea wilt, f.sp variability.